Citrus fruit : biology, technology and evaluation - Ladaniya, Milind (Amsterdam ; Boston ; London : Academic, 2008)
Citrus rank among top three fruits of the world with respect to area and production. Grown commercially in more than 140 countries around the world, world production of citrus fruit has experienced continuous growth in the last decades of the twentieth century with total annual citrus production over 105 million tons between 2000 and 2004. These fruits are commercially important contributing $6-8 billion (US) annually to the world economy and providing jobs to millions of people around the world in harvesting, handling, transportation, storage and marketing. Post harvest biology and technology of citrus fruits is gaining importance as the therapeutic value of citrus fruits is realized and supported by the increase in health awareness among the general public. The purpose of this book is to provide the most comprehensive reference on citrus fruit biology, biotechnology and quality. Basic and applied scientific information is interwoven to serve the researcher, marketer, scientist, nutritionist, or dietician. With discussions of fruit morphology, anatomy, physiology and biochemistry and chapters on growth phases, maturity standards, grades and physical and mechanical characteristics of citrus trees, this book provides the foundation for understanding growth, harvest and post harvest aspects of these important plants. Insect-pests and diseases, irrigation, nutrition and rootstocks are also explored. * Provides practical tips for post harvest management. * Includes all aspects of citrus fruit biology, technology and quality evaluation. * Discusses biotechnological applications and potential fresh citrus fruit quality improvement * Evaluates medicinal and therapeutic applications and recent clinical findings * Exhaustive glossary included.
FINAL: -- 1) Introduction- An Overview -- 2) Commercial fresh citrus cultivars and major producers -- 3) Post harvest losses -- 4) Pre-harvest factors affecting fruit quality and post-harvest life -- 5) Fruit morphology, anatomy and physiology -- 5.1) Fruit morphology -- 5.2) Fruit anatomy -- 5.3) Fruit physiology -- 6) Fruit biochemistry -- 6.1) Carbohydrates -- 6.2) Organic acids -- 6.3) Nitrogenous compounds -- 6.4) Enzymes -- 6.5) Lipids, waxes and other related compounds -- 6.6) Pigments -- 6.7) Phenolics, Flavonoids and limonoids -- 6.8) Vitamins -- 6.9) Inorganic constituents -- 6.10) Volatiles -- 7) Growth, maturity, grade standards and physico-mechanical characteristics of fruit -- 7.1) Growth and development -- 7.2) Maturation -- 7.3) Indices of maturity, fruit grades and standards -- 7.4) Physical and mechanical characteristics -- 8) Harvesting -- 9) Preparation for fresh fruit market -- 9.1) Degreening -- 9.2) Packinghouse operations -- 9.3) Post harvest treatments- Coatings, PBRs & other chemicals -- 10) Packaging -- 10.1) Containers and other packaging materials -- 10.2) Film wrapping -- 10.3) Modified atmosphere packaging -- 11) Pre-cooling -- 12) Storage systems and response of citrus fruits -- 12.1) Refrigerated storage -- 12.2) Controlled atmosphere and hypobaric storage -- 12.3) Evaporative and other natural systems -- 12.4) Ambient storage -- 13) Transportation -- 14) Domestic marketing and distribution systems -- 15) Irradiation -- 16) Postharvest diseases and management -- 16.1) Post harvest diseases -- 16.2) Pesticides, residues and tolerances -- 16.3) Organic post-harvest management -- 16.3.1) Bio-agents -- 16.3.2) Botanicals and other non-hazardous methods -- 16.3.3) Physical methods -- -- 17) Physiological disorders and management -- 18) Postharvest treatments for insect control -- -- 19) Fruit quality control, evaluation and analysis -- 19.1) Quality control and assurance systems -- 19.2) Quality evaluation and instruments -- 19.3) Fruit analysis -- 20) Nutritional and medicinal value of citrus -- 21) Biotechnological applications in fresh citrus fruit -- 22) World fresh citrus trade -- 22.1) Exports and World trade -- 22.2) Quarantine issues.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Citrus fruits; Citrus fruit industry; Agrumes; Agrumes -- Industrie; citrus fruit; TECHNOLOGY & ENGINEERING -- Agriculture -- General; GARDENING -- Fruit; Citrus fruit industry; Citrus fruits; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.